THE EFFECT OF INDONESIAN TAXPAYERS' TAX LITERACY LEVEL MODERATED BY VOLUNTARY COMPLIANCE, TAX SYSTEM EFFECTIVENESS, AND BROADENING THE TAX BASE ON INCREASING THE TAX RATIO IN INDONESIA:CASE STUDY ON INDIVIDUAL TAXPAYERS (WPOP) IN DKI JAKARTA PROVINCE - Subur Harahap (RADJA PUBLIKA, 2025)
Indonesia's tax ratio remains below the average for developing countries, despite its substantial tax potential. One factor contributing to this low tax ratio is the public's level of tax literacy. This article examines the relationship between tax literacy and the tax ratio, using theoretical and empirical approaches. The study results indicate that increased tax literacy, after being moderated by voluntary compliance, tax system effectiveness, and the tax base, has a significant positive impact on the tax ratio.